Cold‐Induced Vomiting of a White‐Tailed Deer (Odocoileus virginianus) by an Invasive Burmese Python (Python bivittatus) in Big Cypress National Preserve, Florida, USA - Travis R. Mangione; Grant S. McCargar; Matthew F. Metcalf; Lisa M. McBride; Eli Suastegui; Josue I. Perez; Cohen W. Eastridge; Matthew F. McCollister; Christina M. Romagosa; Amanda M. Kissel; Amy A. Yackel Adams; Mark R. Sandfoss (Ecology and Evolution, 2025)
ABSTRACT The Burmese python (Python bivittatus) is native to Southeast Asia and has an established invasive population throughout South Florida. As part of the effort to understand invasive python biology and potential impacts to the native ecosystem, we have been using radio‐telemetry to investigate feeding rates of adult female pythons. The body size and gape of adult Burmese pythons enable them to consume large native prey items including, but not limited to, white‐tailed deer (Odocoileus virginianus). As an ectothermic species, Burmese pythons' physiological processes, including digestion, are temperature dependent, which may limit their potential invasive range. The low temperature threshold for python digestion is thought to be 20°C within a laboratory setting. Here, we detail an observation of a radio‐telemetered female Burmese python that ingested an adult white‐tailed deer, retained the deer within the digestive tract for 10 days, and then vomited the deer coinciding with a drop in air temperature as low as 9.4°C. The python survived the vomiting and was alive at the time of publication. To our knowledge, this is the first observation of a free‐ranging Burmese python vomiting a deer within the invasive range without direct disturbance from humans at the time of vomiting. This observation provides additional evidence regarding the limits of thermal tolerance, digestion, and feeding habits of invasive Burmese pythons.